1990
DOI: 10.1007/bf00012108
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the hatching ofStreptocephalus macrourus Daday (Crustacea; Eubranchiopoda) eggs

Abstract: A major drawback to the use in aquaculture of members of the Eubranchiopoda from temporary pool environments is that their eggs do not hatch readily. An investigation of the factors influencing the hatching of eggs of the fairy shrimp Streptocephalus macrourus, showed that light was the only factor of those investigated that was obligatory for hatching. It was found that eggs which had not been desiccated hatched successfully in the presence or absence of adults, while those which had been desiccated showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
3
21
1
Order By: Relevance
“…As to hatching, the events in the pool and in the pond showed that the species responds not to a single but to combined stimuli, as suspected in other species (Brown & Carpelan, 1971) . Moreover, dessiccation is not a pre-requisite for development, in line with previous results (Lowndes, 1993 ;Castle, 1938 ;Avery, 1939 ;Dexter & Ferguson, 1943 ;Hall, 1953Hall, , 1961Prophet, 1963 ;Broch, 1965 ;Mitchell, 1990) . Both assumptions receive further support from the hatching pattern in the pond : nauplii predictably appear after thawing, as soon as temperature reaches suitable values, and in autumn after dilution by the first summer rains .…”
Section: Discussionsupporting
confidence: 78%
“…As to hatching, the events in the pool and in the pond showed that the species responds not to a single but to combined stimuli, as suspected in other species (Brown & Carpelan, 1971) . Moreover, dessiccation is not a pre-requisite for development, in line with previous results (Lowndes, 1993 ;Castle, 1938 ;Avery, 1939 ;Dexter & Ferguson, 1943 ;Hall, 1953Hall, , 1961Prophet, 1963 ;Broch, 1965 ;Mitchell, 1990) . Both assumptions receive further support from the hatching pattern in the pond : nauplii predictably appear after thawing, as soon as temperature reaches suitable values, and in autumn after dilution by the first summer rains .…”
Section: Discussionsupporting
confidence: 78%
“…This is particularly apparent in the case of the rare T cancriformis, which has markedly declined since the 1950's . In the present study, as in others (Minkoffet al ., 1983 ;Mitchell, 1990 ;Murugan & Dumont, 1995 ;Seaman et al ., 1991 ;Takahashi, 1977), light was shown to be a key factor in inducing hatching in branchiopods including Notostraca .…”
Section: Discussionmentioning
confidence: 99%
“…Hatching success in darkness was about one order of magnitude lower than under light (Figure 4) . It is possible that the short exposures to light during the daily microscopic examination, of the eggs induced hatching of some of the dark-treated eggs, since according to Mitchell (1990), a 10 minute exposure to light may induce hatching of some eggs in anostracan branchiopods. All other hatching experiments were carried out under continuous light .…”
Section: Hatching Requirementsmentioning
confidence: 99%
“…The optimal hatching temperature range ( 14-20°C) for S. macrourus from Bloemfontein (Orange Free State, South Africa), measured by Mitchell (1990) does not correspond with the mean daily temperatures in the Botswana sites during the wet season (24-26°C). This discrepancy cautions us in using laboratory results of temperature requirements for hatching to explain actual species distributions, since thermal requirements may merely reflect local adaptation and not necessarily the amplitude of thermal conditions under which all members of the species may exist.…”
Section: Discussionmentioning
confidence: 99%